2006
DOI: 10.1103/physrevlett.97.075001
|View full text |Cite
|
Sign up to set email alerts
|

Active-Feedback Control of the Magnetic Boundary for Magnetohydrodynamic Stabilization of a Fusion Plasma

Abstract: Stable operation with control on magnetohydrodynamic modes has been obtained in the modified reversed field experiment employing a set of 192 feedback controlled saddle coils. Improvements of plasma temperature, confinement (twofold), and pulse length (threefold) and, as a consequence of the magnetic fluctuation reduction, strong mitigation of plasma-wall interaction and mode locking are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 31 publications
5
89
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11] In RFPs, apart from the first observation of RWM reported in HTBX1C in 1988, 12 numbers of studies have been reported in recent years, both experimentally and theoretically; [13][14][15][16][17][18][19] in particular, the successful feedback control of multiple unstable RWMs has shown to be achieved by the equipments implemented in the experiments. [17][18][19] For instance, in RFX-mod 20 experiments, the observations give an evidence that the system of the active control has a sufficient efficiency and a large flexibility 18 and therefore can provide an excellent environment to apply and/or to test RWM physical modeling and various control scenarios, 21 which can further provide a better understanding for RWM physics and the control strategy.…”
Section: Introductionmentioning
confidence: 94%
“…[3][4][5][6][7][8][9][10][11] In RFPs, apart from the first observation of RWM reported in HTBX1C in 1988, 12 numbers of studies have been reported in recent years, both experimentally and theoretically; [13][14][15][16][17][18][19] in particular, the successful feedback control of multiple unstable RWMs has shown to be achieved by the equipments implemented in the experiments. [17][18][19] For instance, in RFX-mod 20 experiments, the observations give an evidence that the system of the active control has a sufficient efficiency and a large flexibility 18 and therefore can provide an excellent environment to apply and/or to test RWM physical modeling and various control scenarios, 21 which can further provide a better understanding for RWM physics and the control strategy.…”
Section: Introductionmentioning
confidence: 94%
“…Since the commissioning of the MHD mode control system, the VS control scheme has been used routinely in the machine experimental sessions, to control both RWMs and TMs, contributing significantly to the successful results obtained in the experimental campaigns [18]. In Fig.…”
Section: Rwm Controlmentioning
confidence: 99%
“…For the active control the perturbed magnetic field measured by the set of sensors facing the plasma surface is used to generate the control signal by the set of active control coils. Such mechanism is extensively studied theoretically [7,8,9,10,11,12] and is successfully applied in the present day fusion devices, allowing operation with the plasma pressures above no-wall limit for tokamaks [13,14,15] and resulting in substantial increase of the plasma discharge duration in RFPs [16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…Several non-resonant harmonics with different toroidal mode numbers (positive and negative according to the sign of the safety factor q of the resonant magnetic surface) are unstable growing on the times comparable with the equilibrium magnetic field penetration through the resistive wall and therefore are classified as RWMs. Experimental studies of RWM control in RFP have shown possibility of simultaneous suppression of several unstable harmonics with different toroidal mode numbers using active feedback [16,17].…”
Section: Introductionmentioning
confidence: 99%